PENJUAL BUNGA DI TEMPAT PEMAKAMAN UMUM KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Sari, Nurmala; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This paper examines specifically in the life of flower sellers at public cemeteries and want to know social capital which the florist uses for his survival when he gets into trouble, as for the research location this a public cemetery in Payung Sekaki District Pekanbaru City. The method used in this study is to use descriptive qualitative method. In this study researcher use data collection techniques observations, interviews, and documentaries. Where researcher in this study discovered some of the social capital that the floris uses in meeting their life needs, these include the first three social capitals, social networks, social norm, and trust. Public florist’s social network Payung Sekaki Districts to bond wicheach otherto create a nice, peaceful environment around starting, exchange information on where to sell flowers, even exchange ideas about their personal lives. Social norm are a set of rules that are expected to be obeyed and followed by the on-shite flower seller although the rule is not written down but is expected thst each seller not trespassing, as an example of pricing flowers, seller should not raise or lower the interest rates without the knowledge of other, since interest prices have been previously agreed upon. Trust is the most important thing among those who sell it without trust is the most likely conflict. Keyword :The Florist, Social Capital, Public Cemetery